Soil Nutrient Analysis Underneath Grewia optiva Population - Sankhyan, H. P.; Dhiman, Jyoti; Chand, Krishan; Prachi; Karishma; Negi, Bhupender (International Journal of Bio-resource and Stress Management, 2021)
The present study was conducted during May and November, 2019 and 2020 and here we quantify the impact of soil nutrient variation on the population growth of Grewia optiva Drummond of different districts with variable climate and heterogeneous soils. The impacts on growth parameters (tree height, crown spread, leaf traits, fruit dimensions) of selected populations of Grewia optiva Drummond statistically analyzed using ANOVA and Pearson correlation coefficient. Five composite soil samples were taken at 15–30 cm depth, on seven selected districts of Himachal Pradesh viz., total 35 samples were analyzed for physiochemical properties. Soil of Mandi district registered with acidic pH as compared to soil pH of other districts. There was significant difference in pH, OC, EC, N, P, K and in Bulk density within selected population of each district. pH range of moderately acidic to moderately alkaline (according to standard soil classification) founded best for growth of this species. There was highly positive correlation observed between Nitrogen and leaf area (0.33), Phosphorus and leaf area (0.45). 100 leaf fresh weight showed highly positive correlation with Nitrogen (0.37) and organic carbon (0.39). 100 leaf dry weight showed highly positive correlation with Nitrogen and Organic Carbon. Crown spread showed highly positive correlation with Organic carbon (0.29), Nitrogen (0.38) and with Phosphorus (0.30). Moderately Positive correlation observed between Potassium and 100 fruit dry weight (0.15).50% of soil texture observed as sandy loamy and sandy clay loamy.